ANTIBACTERIAL ACTIVITY OF N-HEXANA, ETHYL ACETAT, AND ETHANOL EXTRACTS OF RED BETEL LEAVES AGAINST ESCHERICHIA COLI IN VITRO - Armansyah, Teuku; Sutriana, Amalia; Hanif, Muhammad (Buletin Veteriner Udayana, 2022)
Red betel plant ( Piper crocatum ) is a plant that has benefits in the treatment of various diseases. This study aimed to determine the antibacterial activity of red betel leaf extracted using n-hexane, ethyl acetate, and 96% ethanol as solvents against the growth of Escherichia coli in vitro. In this study, 5 concentrations of red betel extract namely 0%, 10%, 20%, 40%, and 60% were used. Chloramphenicol disc was used as a positive control. Antibacterial activity was examined using Kirby-Bauer method. The data were analyzed. The results showed that no inhibition zone was formed around the discs containing n-hexane and 96% ethanol extract, while the ethyl acetate extract at concentrations of 0%, 10%, 20%, 40%, and 60% showed inhibition zone with average diameter were 0 ± 0.8, 97 ± 0.40; 11.61 ± 0.47; 13.4 ± 0.98; 17.56 ± 0.62, respectively. The ethyl acetate extract is able to inhibit the growth of E. coli while the n-hexane and 96% ethanol extracts are unable to inhibit the growth of E. coli in vitro. Further research is needed to examine the effect of red betel ethyl acetate extract against E. coli in vivo .